1998
DOI: 10.1016/s0006-3495(98)77932-9
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic Properties of Living Embryonic Tissues: a Quantitative Study

Abstract: A number of properties of certain living embryonic tissues can be explained by considering them as liquids. Tissue fragments left in a shaker bath round up to form spherical aggregates, as do liquid drops. When cells comprising two distinct embryonic tissues are mixed, typically a nucleation-like process takes place, and one tissue sorts out from the other. The equilibrium configurations at the end of such sorting out phenomena have been interpreted in terms of tissue surface tensions arising from the adhesive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
445
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 448 publications
(488 citation statements)
references
References 38 publications
41
445
2
Order By: Relevance
“…On the other hand, during bone development, cellular differentiation into bone forming osteoblasts occurs within a soft matrix in the range of 100−1000 Pa shear modulus. 64,65 Previous studies also showed that in vitro osteogenic differentiation can be supported on soft hydrogel matrices, which have similar stiffness to developing bone. 66,67 The gene expression results obtained from PA/PEG composite system also pointed to similar conclusions showing that the optimal design of a material for the desired cellular outcome requires the consideration of multiple factors since cells can sense complex niche cues, and these signals can direct cell fate in an interactive manner.…”
Section: Biomacromoleculesmentioning
confidence: 99%
“…On the other hand, during bone development, cellular differentiation into bone forming osteoblasts occurs within a soft matrix in the range of 100−1000 Pa shear modulus. 64,65 Previous studies also showed that in vitro osteogenic differentiation can be supported on soft hydrogel matrices, which have similar stiffness to developing bone. 66,67 The gene expression results obtained from PA/PEG composite system also pointed to similar conclusions showing that the optimal design of a material for the desired cellular outcome requires the consideration of multiple factors since cells can sense complex niche cues, and these signals can direct cell fate in an interactive manner.…”
Section: Biomacromoleculesmentioning
confidence: 99%
“…b measurements in (Forgacs et al, 1998) are for spherical aggregates of embryonic chick liver cells Thomas et al, 2005)). We estimate the packing density to be n * = 0.8 (see Powers et al (2002))…”
Section: Parametersmentioning
confidence: 99%
“…Relatively few data are available for the mechanical properties of embryonic tissues (Forgacs et al, 1998;Davidson et al, 1999;Zamir et al, 2003;Zamir and Taber, 2004). Some measurements indicate that embryonic tissues are more linear than mature tissues, and some investigators have suggested that embryonic epithelia behave as a viscous fluid during the slow process of morphogenesis (Forgacs et al, 1998;Beysens et al, 2000).…”
Section: Materials Propertiesmentioning
confidence: 99%